Analysis of Factors That Affect Community Participation on City without Slums Program (KOTAKU) in Percut Sei Tuan District Deli Serdang Regency - Nenny Rosalinda Siburian; Erika Revida; Suwardi Lubis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The City without Slums (KOTAKU) program is one of the government's strategic efforts to accelerate the handling of slums in Indonesia and support the "100-0-100 Movement", which is 100 percent universal access to drinking water, 0 percent slums, and 100 percent access to proper sanitation. Efforts to handle slums by the government of Deli Serdang Regency began with the identification of the location of slums and the determination of the location of slums through the Decree of the Regent of Deli Serdang No: 413.23/2347 Year 2015 slum area of 461 ha spread across 56 locations of villages, in 19 districts in Deli Serdang. The problem of community participation shows that the involvement of community participation in the KOTAKU Program is still low, this can be seen from the documentation of the list of attending KOTAKU activities in 2019. This study aims to analyze the factors that affect community participation in the KOTAKU Program in Percut Sei Tuan District. The analysis method used in this study is to use a descriptive quantitative approach. The data source used consists of 2 types of data, namely primary data and secondary data. The number of respondents to the study as many as 80 people. The results of this study showed that the factors that influence community participation in the KOTAKU Program in Percut Sei Tuan subdistrict are factors of upper middle age, high school graduation education level, length of work in a week, and understanding positive and significant influence while the factors of long stay and income have a positive and insignificant effect on community participation in the KOTAKU Program.